Pilihan Desain Penyelesaian Sengketa Kewenangan Lembaga Negara - Ahmad Siboy (De Jure: Jurnal Hukum dan Syari'ah, 2022)
Abstract: State institutions were established in order to support the work of the state and government in providing services to the people. Each State institution must be in a unidirectional, synergic, and solid working rhythm. However, in practice, each state institution is fighting for authority between one institution and another. This research is based on the formulation of what causes the Dispute of Authority of State institutions and how the design or pattern of resolution is. This study aims to analyze the root causes of disputes over state institutions' authority and find the design for their resolution. Design in dispute resolution is an important effort to find and formulate ways to end disputes between the parties, such as mediation, reconciliation, negotiation, or through the competent court, for that matter. This type of juridical-normative research is the type of research used in this study. The results showed that conflicts of authority between state institutions occurred due to non-explicit arrangements regarding the position and authority of State institutions. There were no institutions that mediated when conflicts occurred and the sectoral ego of each institution. The settlement design and pattern that can provide legal certainty and protection for every State institution is the settlement through the formation of a particular institution or authority to an already established State institution. With a note that the institution that will judge is not included in the object of the dispute.Keywords: state institutions; dispute; authority.Abstrak: Lembaga Negara didirikan dalam rangka untuk menunjang kerja kenegaraan dan pemerintahan dalam memberikan pelayanan kepada rakyat. Tiap lembaga Negara harus berada dalam irama kerja yang searah, sinergis dan solid. Namun dalam prakteknya, masing-masing lembaga negara justru berebut kewenangan antara lembaga yang satu dengan yang lainnya. Penelitian ini berpijak pada rumusan masalah tentang apa penyebab terjadinya Sengketa Kewenangan lembaga Negara dan bagaimana desain atau pola penyelesaiannya. Penelitian ini bertujuan untuk menganalisis akar terjadinya Sengketa Kewenangan Lembaga Negara serta menemukan desain penyelesaiannya. Desain dalam penyelesaian sengketa menjadi upaya penting untuk mencari dan merumuskan cara-cara mengakhiri sengketa yang timbul diantara para pihak, seperti mediasi, rekonsiliasi, negosiasi, ataupun melalui pengadilan yang berwenang untuk itu. Jenis penelitian yuridis-normatif merupakan jenis penelitian yang digunakan dalam penelitian ini. Hasil penelitian menunjukkan bahwa konflik kewenangan antar lembaga negara terjadi karena pengaturan tentang kedudukan dan kewenangan lembaga Negara yang tidak eksplisit, tidak terdapat lembaga yang memediasi ketika terjadi konflik serta ego sektoral masing-masing lembaga. Desain dan pola penyelesaian yang dapat memberikan kepastian dan perlindungan hukum yang adil bagi setiap lembaga Negara ialah penyelesaian melalui pembentukan lembaga khusus atau penambahan kewenangan pada lembaga Negara yang sudah terbentuk dengan catatan bahwa lembaga yang akan mengadili tidak termasuk dalam objek sengketa.Kata Kunci: lembaga negara; sengketa; kewenangan.